Unilateral Facial Nerve Paralysis in a 13-Year-Old: A Case of Bell’s Palsy with Incidental Sinusitis - Yanamadala, Pavan Kumar; Bhushan, Muddana Phani Ramana; Lalam, Mounika; Lahkar, Manisha; Yoganandam, Suharika; Danduprolu, Satish (Indian Journal of Pharmacy Practice)
Bell’s palsy is an acute, idiopathic paralysis of the peripheral facial nerve, resulting in sudden unilateral facial weakness. It is often associated with viral infections, particularly herpes simplex, and is more common in adults than children. This case is notable as it involves a 13-year-old male with no prior illness or risk factors. A previously healthy 13-year-old male suddenly developed left-sided facial weakness, including an inability to fully close his left eye and a drooping mouth, without any history of trauma or illness. Neurological examination revealed left-sided facial nerve palsy, lagophthalmos, and Bell’s phenomenon, with other cranial nerves unaffected. CT imaging ruled out intracranial abnormalities but showed bilateral maxillary and ethmoid sinusitis. A diagnosis of Bell’s palsy was made based on clinical presentation and the exclusion of other conditions. The patient received a treatment regimen of 20 mg oral Prednisolone, 1000 mg Valacyclovir, and methylcobalamin. Supportive care included lubricating eye drops, protective eye taping during sleep, and physiotherapy for facial exercises. The patient was advised to return for reassessment in five days. Pediatric Bell’s palsy usually has a positive prognosis, with most cases resolving within weeks to months. Early corticosteroid and antiviral treatment may enhance recovery. This case highlights the urgent need for prompt diagnosis and intervention in pediatric Bell’s palsy to prevent complications and ensure optimal recovery. A thorough neurological assessment and appropriate imaging are essential to rule out other causes of facial paralysis.
Keywords: Bell’s palsy; Pediatric facial paralysis; Corticosteroid therapy; Valacyclovir; Neurological evaluation